Demokratiserande læringsprosessar : - nursing students' user experiences and contributions in exam and practice preparation - Bruland, Inger Oline (Nordisk Tidsskrift for Helseforskning, 2023)
Studies on students' experiences of informal user participation in higher education are in demand. It is desirable that the students participated in democratizing learning and assessment processes, since they have first-hand experience of what is important to them. The purpose of the study was to explore and describe how nursing students in the third year of study experience their own participation in the theoretical subject of mental health work. Data were collected in focus group interviews with sixteen students and analyzed through qualitative content analysis. The findings were discussed in detail in how nursing students experience their own user participation within the autonomy they have in the nursing education's theoretical learning initiatives. Students experience that certain framework factors, such as large classes, challenge the processes. Students participate through their learning strategies and various forms of learning. User participation is greatest when the students work in small groups where they get to practice practically on the basis of written cases with guidance from the teacher.
Keywords: user participation; Democratizing learning processes; Mental health work; Deep learning